KARAKTERISTIK GAYA KEPEMIMPINAN PEREMPUAN DALAM OGANISASI ISLAM (STUDI PADA UNIVERSITAS MUHAMMADIYAH MALUKU UTARA DAN INSTITUT AGAMA ISLAM NEGERI IAIN TERNATE) - Fadhliah M Alhadar; Adnan Rajak; Rahayu Togubu (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2019)
The objectives of this study are: (1) To find out and analyze the characteristics of women's leadership styles in Islamic organizations at the University of Muhammadiyah North Maluku and the State Islamic Institute of Ternate (IAIN); (2) To find out the influence of women's leadership style on students at Muhammadiyah University of North Maluku and the State Islamic Institute of Ternate (IAIN) ; (3) To find out and analyze the learning process and the application of women's leadership regulations at the University of Muhammadiyah North Maluku and the State Islamic Institute (IAIN) Ternate. The tools used triangulation observation, intervieuws, documentation with the Miles and Haberman analysis model that starts from the data reduction, data display, and verification or conclusion stages. The results showed that: (1) the characteristics of women's leadership styles, at the University of Muhammadiyah North Maluku and the State Islamic Institute of Ternate (IAIN) were considered good; (2) In addition, the leadership style of women in the two educational institutions, is very influential in general and especially students in motivating, and providing development in the learning process and encouragement, in order to be able to hone their abilities, and make female leaders as patrons for female leaders will come; (3) As in the process of enforcement, women leaders based on regulatory agencies specified in the legislation-u ndang Education System. Meanwhile the steps taken in the learning process in class go through three stages, namely the initial activity , the core activity, and the final activity . At these stages can stimulate the learning process is most students to learning in the classroom implementation of the Most students become active and raised their interaction.